Research on Improved Fault Current Analysis Method for Flexible Direct Current Power Grid Considering Alternating Current Feed - Sun, Yinfeng; Xiong, Xin; Wang, Zhenhao; Li, Guoqing; Wu, Xueguang; Wang, Weiru (Frontiers in Energy Research, 2021)
Flexible DC grid can realize large-scale renewable energy wide-area coordinated complementation and reliable power transmission. It is an important development direction for high-voltage and large-capacity flexible DC transmission in the future. The short-circuit current of the DC line is one of the important basis for the selection of key main equipment parameters such as converter valves, DC circuit breakers and reactors in the flexible DC grid. In this paper, a flexible DC grid equivalent circuit network model with AC feed-in is established. Aiming at the monopolar ground fault of the flexible DC grid grounded through the metal loop, an optimized traditional matrix calculation method is proposed to obtain the accurate line fault current value. On this basis, with actual engineering as the background, the equivalent circuit model of the four-terminal bipolar flexible DC power grid is established, and the influence of grounding position, grounding parameters and current-limiting reactor on the fault current of the DC line is analyzed. Finally, PSCAD simulation verifies the effectiveness and accuracy of the proposed method. The method proposed in this paper can provide the necessary basis and reference for the selection of flexible DC grid equipment.